Alternative Fermented Soy-Based Beverage: Impact of Inulin on the Growth of Probiotic Strains and Starter Culture - Wellison Amorim Pereira; Anna C. M. Piazentin; Thamires M. S. da Silva; Carlos M. N. Mendonça; Elias Figueroa Villalobos; Attilio Converti; Ricardo Pinheiro S. Oliveira (Fermentation, 2023)
The number of people with dietary restrictions on dairy products has increased significantly due to lactose intolerance/allergy or adoption of vegan diets. Organic acid-producing probiotics have been used in fermented beverages, such as those based on soy, with good results. Such molecules have in fact been described for their role in sensory analyses and benefits to human health. Therefore, this study suggested the evaluation of an alternative soy extract-based beverage that could act as a functional food. For this purpose, products and biomass concentrations were monitored throughout soy extract fermentation through acidification kinetics and cell count. The effect of inulin on the growth of the probiotic strains Bifidobacterium longum and Lactobacillus acidophilus in co-culture with Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus was evaluated (technical replicates). It was observed that the addition of inulin reduced the time of fermentation by L. acidophilus, while no statistically significant effect was observed in the post-acidification period. In B. longum fermentation, the process did not change in the presence of inulin, but there was a significant increase in viability and survival in the post-acidification period. Therefore, it can be concluded that the strains studied can be used in the formulation of soy-based drinks and that inulin positively influenced the viability of both probiotics in fermented drinks tested.